Pengaruh Corporate Social Responsibility pada Nilai Perusahaan dengan Kinerja Lingkungan Sebagai Pemoderasi - Lingga, Veronica Padma; Wirakusuma, M. G. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.04.TAHUN 2019DO - 10.24843/EEB.2019.v08.i04.p05, 2019)
This study aims to determine the effect of Corporate Social Responsibility on the value of the company with environmental performance as moderating. This research was conducted on basic industrial and chemical sector companies, various industries, and mining listed on the Indonesia Stock Exchange for the period 2015-2017. The sampling technique in this study was taken based on non-probability sampling method with a purposive sampling technique so as to produce a sample of 43 companies. The data analysis technique used in this study was moderated regression analysis. Based on the results of the analysis it was found that Corporate Social Responsibility had a positive effect on firm value. The results of this study also show that environmental performance is not able to moderate the influence of Corporate Social Responsibility on firm value, which is due to good environmental performance that may not necessarily have a positive impact or benefits for investors.